PENERAPAN PEMBELAJARAN PEMECAHAN MASALAH MODEL POLYA UNTUK MENYELESAIKAN SOAL-SOAL APLIKATIF POKOK BAHASAN SEGI EMPAT PADA SISWA KELAS VII F SMP NEGERI 9JEMBER SEMESTER GENAP TAHUN AJARAN 2013/2014 - Pratama, Septiyan Roby; Hobri, H; Fatahillah, Arif (KadikmA, 2015)
Abstract. Polya model is one of problem solving model that help the students for solving applicative math problems. Furthermore, Polya defines problem solving as an attempt to find the way out from one difficultness, and reach the unreachable objective that cannot be solved at once. The research aims are (1) how do the Polya problem solve appliment solve the applicative questions, (2) how do the activities of the students as long as Polya problem solve appliment occur to solve the applicative questions, (3) how do the student learn finishment after Polya problem solving appliment occur to solve the applicative question. The results showed improvement of the results of work of students using the Polya Model to solve the problem about applicative questions from first cycle to the next cycle. The research subjects are for analyzing qualitative and quantitative data. The research result shows that category activity in the ârexamineâ and âpresentationâ are the lowest. The learning activity result in the first cycle are 64,1% student complete and not fulfill the classical absorptive power because of â¤ 70%. The second cycle result is increasing of learning result for 79,49% which means has reached classical complement. So, the research has fulfilled the research aims. Key Words : Polya Model Problem Solving, Students Activity,Result of Studentsâs Learning.